Nilai Pendidikan Karakter Pada Novel Pak Guru Karya Awang Surya - Izati, Siti Nihla (Universitas Muhammadiyah Prof. DR. HAMKA, 2016)
This study aims to find the values of character education contained in the novel Pak Guru Awang Surya work associated with structural genetic studies. Research disclosure of the educational value of these characters using qualitative research content analysis techniques. For qualitative research, data taken from quotes novel formula Pak Guru Awang works Surya in paragraph form. Content analysis technique used to systematically analyze the data or contents as well as text messaging story. The value of character education in the novel Pak Guru Awang works Surya found as many as 67 paragraphs, or 76.13%, and that does not contain the value of character education there are 21 paragraphs, or 23.86%, of which the relationship to God as much as 4 paragraphs or 59.67%, the relationship of neighbor as much as 15 or 22.38%, the relationship with yourself as much as 34 paragraphs, or 50.74%, the relationship of the nationality as much as 4 or 59.67%, and the relationship to the environment as much as 10 or 14.92%. The value of character education appears most is the value of character education relationship to yourself with a percentage of 50.74% is thus novel Pak Guru Awang Surya work is much describes the value of character education in relation to ourselves whole chapters and paragraphs that have been reduced.  values character education